Contemporary territorial management among the Nahuas of Tlamacazapa, state of Guerrero, Mexico - Montes de Oca Hernández, Acela (2024)
Territorial management, as an alternative tool for the controversial concept of development, offers land management plans to regulate anthropogenic activities and protect ecosystems. However, institutional measures continue to bring together the participation of territorial actors and to be challenged by increased environmental crises. The above motivates the following question: What is the relationship between territorial management and human capacities? This article aims to analyze the contemporary territorial management of the Nahuas of Tlamacazapa from the human capacities perspective, focusing on the family, cultural, and environmental spheres. This was researched in poor Nahua families and their ways of occupying, managing, and taking advantage of the territory based on their abilities, knowledge, and skills. The methodology used was qualitative. Ontological dialogues help specify the relationship between study families and the territory. The materialization of ontological knowledge in the territory intends to extend the discussion of contemporary territorial management.